The effects of vegetarian diets on bone health: A literature review - Falchetti, Alberto; Cavati, Guido; Valenti, Roberto; Mingiano, Christian; Cosso, Roberta; Gennari, Luigi; Chiodini, Iacopo; Merlotti, Daniela (Frontiers in Endocrinology, 2022)
The adoption of a vegetarian-type diet has become increasingly popular in recent years especially for its numerous health benefits such as reducing the incidence of obesity, diabetes, hypertension, cardiovascular diseases and some types of cancer. However, the rather restrictive typology of this diet have raised some doubts about a possible deficiency of some nutrients and an increased risk of osteoporosis. Although there are conflicting data on the effects of the vegetarian diet on bone health and fracture risk, in vegetarians it is always advisable to follow some dietary recommendations such as an adequate intake of calcium and vitamin D, through the intake of natural, fortified foods or specific supplements, an adequate protein intake and abundant intake of fruit, vegetables, as well as an adequate intake of vitamin B12.